PENGARUH KENAIKAN PANGKAT TERHADAP PERENCANAAN KARIER DAN KINERJA PEGAWAI NEGERI SIPIL DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (STUDI PADA KANTOR REGIONAL XI BKN MANADO) - Monareh, Pascal; Olivia S. Nelwan; Frederik G. Worang (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2025)
This study aims to analyze the effect of promotion on career planning and performance of Civil Servants (PNS) at Regional Office XI of the National Civil Service Agency Manado, with job satisfaction as an intervening variable. The study employed a quantitative approach through a survey of 83 civil servants and analyzed using Partial Least Squares–Structural Equation Modeling. The results show that promotion does not have a significant direct effect on career planning or employee performance, but has a positive and significant indirect effect through job satisfaction. Additionally, promotion has a direct positive effect on job satisfaction, while job satisfaction directly and positively influences career planning and performance of civil servants.